NPS Policy Network Write-Shop Entebbe - CGIAR (CGIAR System Organization, 2023)
The CGIAR Initiative on National Policies and Strategies organized a three-day Policy Network Write-Shop, the second in the policy network series, from 14th -16th November 2023 at Entebbe, Uganda. The first was the Policy Network and Engagement Workshop in Nairobi in June 2023.